New determinaion of the D-0 -> K-pi(+)pi(0) and D-0 -> K-pi(+)pi(+)pi(-) coherence factors and average strong-phase differences - Libby, J; Malde, S; Powell, A; Wilkinson, G; Asner, D; Bonvicini, G; Briere, R; Gershon, T; Naik, P; Pedlar, T; Rademacker, J; Ricciardi, S; et al. (2014)
Measurements of the coherence factors (RKππ0 and R K3π) and the average strong-phase differences (δDKππ0 and δDK3π) for the decays D0→K -π +π0 and D0→K -π +π +π - are presented. These parameters are important inputs to the determination of the unitarity triangle angle γ in B ∓→DK ∓ decays, where D designates a D0 or D-0 meson decaying to a common final state. The measurements are made using quantum correlated DD- decays collected by the CLEO-c experiment at the ψ(3770) resonance, and augment a previously published analysis by the inclusion of new events in which the signal decay is tagged by the mode D→KS0π+π- The measurements also benefit from improved knowledge of external inputs, namely the D0D-0 mixing parameters, rDKπ and several D-meson branching fractions. The measured values are RKππ0=0.82±0.07, δDKππ0=(164-14+20)°, RK3π=0.32-0.28+0.20 and δDK3π=(225-78+21)°. Consideration is given to how these measurements can be improved further by using the larger quantum-correlated data set collected by BESIII. © 2014 The Authors.